Laccases in Food Industry: Bioprocessing, Potential Industrial and Biotechnological Applications - Mayolo-Deloisa, Karla; González-González, Mirna; Rito-Palomares, Marco (Frontiers in Bioengineering and Biotechnology, 2020)
Laccase is a multi-copper oxidase that catalyzes the oxidation of one electron of a wide range of phenolic compounds. The enzyme is considered eco-friendly because it requires molecular oxygen as co-substrate for the catalysis and it yields water as the sole by-product. Laccase is commonly produced by fungi but also by some bacteria, insects and plants. Due it is capable of using a wide variety of phenolic and non-phenolic substrates, laccase has potential applications in the food, pharmaceutical and environmental industries; in addition, it has been used since many years in the bleaching of paper pulp. Fungal laccases are mainly extracellular enzyme that can be recovered from the residual compost of industrial production of edible mushrooms as Agaricus bisporus and Pleurotus ostreatus. It has also been isolated from microorganisms present in wastewater. The great potential of laccase lies in its ability to oxidize lignin, one component of lignocellulosic materials, this feature can be widely exploited on the pretreatment for agro-food wastes valorization. Laccase is one of the enzymes that fits very well in the circular economy concept, this concept has more benefits over linear economy; based on "reduce-reuse-recycle" theory. Currently, biorefinery processes are booming due to the need to generate clean biofuels that do not come from oil. In that sense, laccase is capable of degrading lignocellulosic materials that serve as raw material in these processes, so the enzyme's potential is evident. This review will critically describe the production sources of laccase as by-product from food industry, bioprocessing of food industry by-products using laccase, and its application in food industry.